Designing for a digital and globalized world : 13th International Conference, DESRIST 2018, Chennai, India, June 3?6, 2018, Proceedings /: 13th International Conference, DESRIST 2018, Chennai, India, June 3?6, 2018, Proceedings. (2018) - Unknown
No abstract available